STRATEGI PENGEMBANGAN JURUSAN EKONOMI ISLAM BERBASIS INPUT, PROSES, OUTPUT DAN OUTCOME PENDIDIKAN - Ratno Agriyanto (At-Taqaddum, 2013)
Department of Economics, Faculty of Shariah Islam has a strategic opportunity to grow and develop into educational institutions that produce a realiable human resource in the field of Islamic economics. However, in the progress of the graduates numbered only 57.121 people or 47% of graduates who obtain employment while the other or 64 graduates (53%) do not get a job. Under such conditions a thorough evaluation of the input, process, out put and outcome of Economics Department of Islamic education must be done before it appears on the existence of stigma perceived Islamic Economics Department can not create quality graduates but could only create unemployment. The purpose of this study is to identify good practices do offer Islamic economics in the development of Islamic Economics Department through the paradigm of input, process, output and outcome research pendidikan. Responden include Students, Faculty, Alumni and Alumni Users. Data analysis using descriptive qualitative. The results recommend to managers of Islamic Economics Department as follows: input paradigm improve the quality of inputs, increase new students with non-academic achievment, improving the compatibility of professional competence of teachers, curriculum improvementin order to accomodate the needs of industry, the head of department more communicative with stakeholders and enhance its position as a motivator, increases content competency-based learning student end. The paradigm of the department to plan activities on a periodic basis and set a measureable output, systematically structure the learning, creative learning model, improve discipline faculty, enhance cooperation, conduct an evaluation of the achievement of the plan periodically. Paradigm output increase graduate GPA, second equip students with competence. Paradigm equip science student outcomes that are relevant to the needs of the industry, to equip students with the moral integrity, professional attitude, entrepreneurship and the ability to adapt quickly to the external environment, equipping students with good language skills, the ability to think conceptually rational, systematic and critical, the ability material presented before the public, negotiation skills, the ability to guide, enhance the ability of students about the contract and Islamic transactions, cost and budgeting, accounting, financial analysis, and computer skilss.